KYRGYZSTAN IN THE CONTEXT OF DIALECTICS OF SUSTAINABLE DEVELOPMENT (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This scientific article analyzes the development of Kyrgyzstan through the prism of the dialectics of sustainable development. To analyze the historical situation in Kyrgyzstan and the way to achieve a stable state of Kyrgyz society in the environmental, economic and social spheres, the dialectical and historical method is used. It is the dialectics of sustainable development that allows states to move along the path of developing stability, harmony of society and nature in today’s realities. The subject of research in this work is consideration of the phenomenon of sustainable development of Kyrgyzstan through the prism of the laws of dialectics and synergetic.The application of the laws and categories of dialectics and synergetic reveals the mechanism of historical development and illustrates what factors exist that influence the role in the development of stabilization and the further sustainable advancement of Kyrgyzstan.
Keywords: civilization, dialectics, synergetic, Kyrgyzstan, sustainable development, society, nature, contradiction, laws, principles.